Role of Financial Service Authorities on Legal Protection of The Sharia Banks Customers in Indonesia - Sri Astutik (Rechtsidee, 2019)
Sharia Bank is a bank that runs its business activities based on sharia principles, in the collection of funds and the distribution of funds, in order to serve the needs of society and improve the standard of living of the people. Various banking problems, such as not yet optimal protection of consumer financial services (bank customers), therefore it is necessary to supervise the operational banking activities. The purpose of bank supervision is to protect the interest of the savers who entrust their funds to the bank. Based in Law Number 21 of 2011 on the Authority of Financial Services, the arrangement and supervision of financial institutions becomes the authority of the Financial Services Authority. This supervision is also applied to banks with sharia principles. In this paper will discuss the Financial Services Authority oversight in the application of the principle of legal protection for customers in sharia banks.